Can creation of separate ministries of animal husbandry, dairies and fisheries bring fresh momentum in growth? - Kumar, Anjani; Verma, Smriti; Padhee, Arabinda K. (2019)
Can the welcome creation of a separate ministry of animal husbandry, dairying and fisheries bring fresh momentum in the growth of allied sectors? There are several challenges to deal with.